A predictive science approach to aid understanding of electrospray ionisation tandem mass spectrometric fragmentation pathways of small molecules using density functional calculations. (14th April 2013) - Galezowska, Angelika; Harrison, Mark W.; Herniman, Julie M.; Skylaris, Chris‐Kriton; Langley, G. John
<x xml:space="preserve">Abstract</x> RATIONALE Tandem mass spectrometry (MS/MS) dissociation pathways can vary markedly between compound classes and can result in challenging and time‐consuming interpretation of the data. Compound, class and substructure specific fragmentation rules for protonated molecules require refinement to aid the structural elucidation process. METHODS The application of a predictive science approach using density functional theory (DFT) calculations has been investigated to estimate the abundances of first‐generation product ions observed using an ion trap mass spectrometer. This has been achieved by application of Boltzmann population theory to electrospray ionisation (ESI)‐MS and MS/MS data. RESULTS Tandem ESI‐MS data for this preliminary study were used to investigate the internal stabilities of protonated species and their product ions. The calculated relative abundances of 11.3%, 96.5%, and 1.1% for the product ion (m/z 192) of three quinazoline structural isomers are compared with the experimental values of 16%, 90% and 0% observed in the first‐generation product ion mass spectra. CONCLUSIONS Close correlation between calculated and experimental data has been demonstrated for these initial data. Applying this approach and establishing fragmentation rules, based on structure specific and common fragmentation behaviour, would improve and expedite the structural elucidation process. Copyright © 2013 John Wiley & Sons, Ltd.